Plane Closed Trajectories on Certain Manifolds with Rotation Metric - Romanov, S. S. (Ukrains’kyi Matematychnyi Zhurnal, 2004)
Trajectories on spherical and toroidal manifolds are studied by methods of infinitesimal and global geometry.